2022
DOI: 10.1016/j.csbj.2021.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Computational challenges in detection of cancer using cell-free DNA methylation

Abstract: Cell-free DNA(cfDNA) methylation profiling is considered promising and potentially reliable for liquid biopsy to study progress of diseases and develop reliable and consistent diagnostic and prognostic biomarkers. There are several different mechanisms responsible for the release of cfDNA in blood plasma, and henceforth it can provide information regarding dynamic changes in the human body. Due to the fragmented nature, low concentration of cfDNA, and high background noise, there are several challenges in its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 151 publications
(144 reference statements)
0
8
0
Order By: Relevance
“…17 Aberrant methylation patterns in ctDNA have been implicated as useful tools for non-invasive cancer detection. [31][32][33][34][35] We detected methylated JAM3 in cfDNA from patients with CCA and biliary diseases, with a sensitivity of 53.3% and specificity of 96.6%.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…17 Aberrant methylation patterns in ctDNA have been implicated as useful tools for non-invasive cancer detection. [31][32][33][34][35] We detected methylated JAM3 in cfDNA from patients with CCA and biliary diseases, with a sensitivity of 53.3% and specificity of 96.6%.…”
Section: Discussionmentioning
confidence: 90%
“…Junctional adhesion molecular 3 has been shown to participate in epithelial‐mesenchymal transition (EMT) in colonic epithelial cells and functions as a tumour suppressor in colorectal cancer 17 . Aberrant methylation patterns in ctDNA have been implicated as useful tools for non‐invasive cancer detection 31–35 . We detected methylated JAM3 in cfDNA from patients with CCA and biliary diseases, with a sensitivity of 53.3% and specificity of 96.6%.…”
Section: Discussionmentioning
confidence: 95%
“…5hmC is the most abundant and stably oxidized product among them, 143 but when compared with the 8% methylated cytosine in the human genome, number of hydroxymethylated cytosines is really tiny with only 0.5 to 1% 144 . Meanwhile, it was reported that in contrast to 5mC, 5hmC‐based profiles are relatively more stable and robust, providing better specificities 145 . Since 5hmC are found to be enriched in enhancers, promoters, and other regulatory elements, it is understandable that changes in 5hmC are associated with changes in gene expression 146–148 .…”
Section: Epigenetic‐based Cancer Liquid Biopsymentioning
confidence: 99%
“…Batch effect from technical, non-biologic variations during sample collection, processing, and preparation can result in erroneous conclusions and hinder the reproducibility and generalizability of findings. [65][66][67][68] This challenge is amplified when combining data sets, 69,70 as we propose, to better power analyses of rare disease states and treatment effectiveness. To minimize batch effect and enhance the validity and reliability of NF1/SWN biomarker research, it is imperative that preprocessing conditions, detailed methodology, and complete analytic pipelines are described and publicly available.…”
Section: Standards For Data Reproducibility and Usabilitymentioning
confidence: 99%